Fermented Plant-Based Milks Based on Chestnut and Soybean: Comprehensive Evaluation of Fermentation Characteristics and Aroma Profiles Using Four Lactic Acid Bacteria Strains - Qingyang Sun; Xiaowen Shi; Yue Zhao; Ruiguo Cui; Yaya Yao; Xiaoyu Liu; Haoran Wang; Li Zhang; Lijun Song (Foods, 2025)
In this study, four lactic acid bacteria (LAB) strains, including Lactiplantibacillus plantarum CICC21790, Lacticaseibacillus casei CICC6117, Lacticaseibacillus rhamnosus ATCC7469, and Limosilactobacillus fermentum CICC22704, were used to ferment a plant-based milk composed of chestnut and soybean. The fermentative characteristics of the four LAB strains and the aroma characteristics of the resulting plant-based milks were systematically investigated. The results showed that all four LAB strains successfully fermented the plant-based milk. The viable cell counts ranged from 7.67 to 8.57 lg CFU mL−1, and pH values were between 3.80 and 4.10. Comprehensive analyses performed using E-nose and HS-GC-IMS revealed distinct aroma characteristics in plant-based milks fermented by different LAB strains. Specifically, LAB fermentation, particularly by the CICC22704, significantly reduced the concentrations of aldehydes (e.g., hexanal, heptanal), thereby diminishing Green aroma characteristics. The increased concentrations of alcohols (e.g., 1-pentanol), ketones (e.g., 2, 3-butanedione) and furan compounds (e.g., 2-pentylfuran) in fermented plant-based milks enhanced Pungent, Creamy, and Fruity aroma characteristics, respectively. Fermentation by CICC21790, ATCC7469, and CICC6117 may result in stronger intensities of these three aroma characteristics compared to fermentation by the CICC22704. For the Fatty aroma characteristic, it was enhanced by CICC21790 fermentation but diminished by ATCC7469, CICC6117, and CICC22704 fermentations.